Integrated water resources management and the right to water security - Howarth, W (2013)
The purpose of this policy brief is to reflect upon global objectives for water management and the way that these relate to national concerns about water in the United Kingdom and, more particularly, England. The brief identifies wide divergence between global calls for the integration of water management, encompassing integrated regulatory approaches, and the limited significance of this as a national legislative concern. Difficult choices need to be made between competing water uses which are mutually incompatible. Significantly, recent measures have placed emphasis on management options that recognize the natural character of the threats involved and the need for sustainable responses that work with nature rather than against it. To the extent that ‘naturalization’ may be seen as an appropriate response to a wider range of water management issues, the policy brief raises the question of whether naturalization rather than integration might serve as a preferable imperative for water management more generally.